An open-labeled study of rebamipide treatment in chronic gastritis patients with dyspeptic symptoms refractory to proton pump inhibitors - Chitapanarux T. (2014)
To assess the efficacy of rebamipide therapy in chronic gastritis patients with refractory dyspeptic symptoms, we enrolled 30 patients with chronic gastritis nonresponsive to the antisecretory medications, proton pump inhibitors. Upper gastrointestinal endoscopy was performed in all patients to confirm and evaluate the severity of gastritis by gastric mucosal injury score and the histology by the updated Sydney system before and after treatment with rebamipide 300 mg daily for 8 weeks. At the end of the study, significant improvement in the scores for symptoms (epigastralgia, stomach heaviness, and abdominal fullness) and endoscopic mucosal injury were observed for all patients. The degrees of neutrophil activity in antrum and mononuclear cell inflammation in both body and antrum significantly decreased from baseline. Improvement of gastritis might be the mechanism by which rebamipide prevents gastric mucosal inflammation. In conclusion, rebamipide treatment improved symptom, endoscopic, and histologic features of chronic gastritis in patients with refractory dyspeptic symptoms. © 2008 Springer Science+Business Media, LLC.